2021
DOI: 10.3389/fclim.2021.610433
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Rainfall and Hydro-Geo-Meteorological Disaster Risk in 1.5, 2.0, and 4.0°C Global Warming Scenarios: An Analysis for Brazil

Abstract: With the inclusion of demographic characteristics of the population living in vulnerable areas, a combination of empirical and climate models was used to project changes to climate and in hydro-geo-meteorological disasters in Brazil. This study investigated the effect of extreme rainfall changes and the risk of floods and landslides under 1.5, 2.0, and 4.0°C global warming levels (GWLs). Projections from a large ensemble of pre-CMIP6 models and different warming levels show a remarkable change in heavy precipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 22 publications
1
21
0
3
Order By: Relevance
“…The projections showed that densely populated areas are the most exposed to landslides and floods. They further noted that the exposure was projected to persist and aggravate for warming above 2.0 • C. The observations by Marengo et al (2021) agreed with the findings of Zhang et al (2018) over monsoon regions where it was projected that 0.5 • C less warming would reduce the risk of population exposure to once-in-20 year extreme precipitation events by 22%-46%. Over China, Chen and Sun (2020) and Wang et al (2020) projected an increase in exposure of about 21.6% under the RCP4.5-SSP2 scenario by the end of the 21st century, despite a projected decline in population, thus stressing the need to address GHG emissions as efforts to minimize exposure to precipitation extremes.…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…The projections showed that densely populated areas are the most exposed to landslides and floods. They further noted that the exposure was projected to persist and aggravate for warming above 2.0 • C. The observations by Marengo et al (2021) agreed with the findings of Zhang et al (2018) over monsoon regions where it was projected that 0.5 • C less warming would reduce the risk of population exposure to once-in-20 year extreme precipitation events by 22%-46%. Over China, Chen and Sun (2020) and Wang et al (2020) projected an increase in exposure of about 21.6% under the RCP4.5-SSP2 scenario by the end of the 21st century, despite a projected decline in population, thus stressing the need to address GHG emissions as efforts to minimize exposure to precipitation extremes.…”
Section: Introductionsupporting
confidence: 64%
“…Chen et al (2020) projected a global increase in population exposure of 2.3% following an increase in surface air temperature to 2.0 • C. Zhao et al (2021) reported that extreme precipitation events and population exposure are projected to increase with warming levels over the Indus River Basin. Marengo et al (2021) studied extreme rainfall and hydro-geo-meteorological disaster risk in 1.5 • C, 2.0 • C, and 4.0 • C global warming scenarios: an analysis for Brazil. The projections showed that densely populated areas are the most exposed to landslides and floods.…”
Section: Introductionmentioning
confidence: 99%
“…In relation to climate change, this research showed that publications on this topic are still incipient for the Pantanal (Marengo 2015;Marengo et al 2021), with a tendency to temporal displacement of rainfall and a reduction in the volume of precipitation with a direct effect on the flood pulse, mainly in terms of amplitude, duration and, consequently, its lateral connectivity and extensions. The first studies related to climatic change in the Pantanal analyzed the large drought during the end of the 1960s and the beginning of the 1970s, as well as the start of the large flooding cycle in the Paraguay River (Collischon et al 2001).…”
Section: Discussionmentioning
confidence: 86%
“…As a consequence of these variations in rainfall predict a reduction of 10% to 20% between 2010 and 2040 (Marengo 2015) were register a decrease of water volume of 16% in the last 20 years in the Paraguay River (Lázaro et al 2020). The effect of the severe drought of 2020 and 2021 on Pantanal and its surroundings, caused hydric stress on vegetation and favored the fires in the Pantanal in 2020 (Marengo et al 2021).…”
Section: Discussionmentioning
confidence: 98%
“…Consequently, thresholds developed for different parts of Serra do Mar could preliminarily be adapted and updated for Pedra Branca, such as the one from Kanji et al (1997). A constant update of these rainfall thresholds is necessary, especially considering the projected increase in the frequency of extreme rainfall events for the south and southeast of Brazil (Marengo et al 2021) and that these equations were created more than 20 years ago.…”
Section: Discussionmentioning
confidence: 99%